Les marchands-banquiers florentins de Lyon et leurs réseaux, entre pratique des affaires et stratégies judiciaires. Le cas Martelli (1567-1574) - Ilario Mosca (Criminocorpus)
The study of the conflict opposing the Florentine company Martelli of Lyon and the merchant native of Alba Giampietro Dusio between 1567 and 1574, with its judicial and extrajudicial aspects, enables understanding the ability of merchants to involve and to take advantage of a multiplicity of institutions and relationship networks. The search for an acceptable solution to the conflict ends up taking precedence over the search for the truth.